Selectivity of Rhodium-Catalyzed Hydroformylation of 1-Octene in a Thermomorphic Solvent System - Shaharun, Maizatul Shima (2010)
The use of temperature dependent multicomponent solvent (TMS) process, in which the catalyst remains as a residue in one of the liquid phases and the product goes preferably to the other liquid phase, can be an enabling strategy of commercial application of hydroformylation processes with high selectivity, efficiency and ease of product separation and catalyst recovery. This paper describes the isomer distribution of the formation of nnonanal and 2-methyloctanal for the rhodium-catalyzed homogeneous hydroformylation of 1-octene using HRh(CO)[P(OPh)3]3 catalyst in TMS-system consisting of propylene carbonate (PC), dodecane and 1,4-dioxane. Effects of the concentration of 1-octene and catalyst, temperature, composition of syngas (H2/CO), total pressure of syngas and ligand to catalyst [P(OPh)3/HRh(CO)(PPh3)3] ratio on the selectivity of the nonylaldehyde products (n/iso ratio) have been measured. Highest selectivity for n-nonanal with average catalyst activity is observed at temperature of 363 K, equimolar of CO/H2, total syngas pressure of 1.5 MPa and ligand/catalyst ratio of 12 in TMS composition of 0.1/0.3/0.6. This study is practically useful for the optimization of n-nonanal production by hydroformylation of 1-octene.